APPLICATION OF NATURAL PLANT GROWTH REGULATOR AND COW BIOURINE ON GROWTH AND YIELD OF SHALLOT IN RAINY SEASON (Allium cepa L.) - Supono Budi Sutoto; Ami Suryawati; Lagiman Lagiman (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2021)
The use of natural hormones of young sweet corn extract, coconut water extract, and banana stem extract and application of cow biourine has been introduced as an innovation to reduce the use of chemical fertilizers to increase the productivity of shallot. This study aims to compare the growth and yield of shallot with chemical fertilizer treatment and that of shallot treated with a combination of the natural hormone and cow urine. The study was conducted from October 2019 to January 2020 in Temon Wetan, Temon, Kulon Progo, Special Region of Yogyakarta using a Complete Randomized Block Design, which consists of two factors and one control (chemical fertilizer). The first factor is a natural hormone: young sweet corn extract, banana stem extract, and coconut water. The second factor is the concentration of cow urine: 30%, 40%, and 50%. Data were subjected to an analysis of variance followed by Duncan’s Multiple Range Test and Orthogonal Contrast at 5% It was revealed that the control group with combined treatments was not significantly different from the growth and yield of shallot of the group with chemical fertilizers. Types of treatments with natural hormone and cow urine concentrations provided the same growth and yield as that of chemical fertilizer.